2011
DOI: 10.1002/pssa.201001160
|View full text |Cite
|
Sign up to set email alerts
|

Towards experimental identification of vacancy complexes in InN

Abstract: In this contribution we present ab initio calculations of positron states and annihilation at vacancies and vacancy complexes in InN. Momentum distributions of annihilating electron-positron pairs in indium (V In ) and nitrogen vacancies (V N ) as well as mixed vacancy clusters are calculated. Based on the modelled data the possibility of their experimental detection and distinction using positron annihilation spectroscopy is discussed. No localization of the positron density is found for isolated V N and V N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The induced uncertainty could in principle cause difficulties for the exact defect identification, as small differences between the different lattice directions are present. 31 Nevertheless, these are minor compared to differences between the calculated spectra of different defect complexes and hence pose no problem in our case. This counts especially when interpreting changes in the momentum distributions rather than absolute values.…”
Section: Summary and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The induced uncertainty could in principle cause difficulties for the exact defect identification, as small differences between the different lattice directions are present. 31 Nevertheless, these are minor compared to differences between the calculated spectra of different defect complexes and hence pose no problem in our case. This counts especially when interpreting changes in the momentum distributions rather than absolute values.…”
Section: Summary and Discussionmentioning
confidence: 83%
“…We compare the experimental spectra to computational momentum distributions integrated over the m-plane. The induced uncertainty could in principle cause difficulties for the exact defect identification, as small differences between the different lattice directions are present 31 . Nevertheless, these are minor compared to differences between the calculated spectra of different defect complexes and hence pose no problem in our case.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of V In – n V N vacancy complexes near the interface speaks for a close proximity of V In and V N prior to complexing, and therefore for highly elevated concentrations of N vacancies in this area. Isolated nitrogen vacancies do not trap positrons in InN 15, 16 and hence escape detection with positron annihilation spectroscopy. Single V N are triply charged donors 20 and act as efficient donors in InN.…”
Section: Resultsmentioning
confidence: 99%
“…Selected results from previous positron studies in InN can be found in Refs. 10–16. In this contribution, we present a systematic study of the point defect landscape in MOCVD growth of InN with varying growth parameters.…”
Section: Introductionmentioning
confidence: 99%